1991
DOI: 10.1597/1545-1569(1991)028<0078:liomiw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Language Input of Mothers Interacting with Their Young Children with Cleft Lip and Palate

Abstract: Maternal language addressed to 1-, 2-, and 3-year-old children with cleft lip and palate was studied. Videotaped interactions were obtained from 23 mother-child dyads (13 mother-cleft lip and palate child dyads, and 13 mother noncleft child dyads) during free play. Results indicated more similarities than differences in maternal language characteristics for the two groups of mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This study showed that infants with CP produced more child vocalization counts from the LENA automated analysis than infants without at 4 to 6 months and 7 to 9 months but not at later ages. This result was unexpected as previous studies have either reported that children with CP produce fewer vocalizations than children without CP (Philips and Kent, 1984; Chapman, 1991; Ha, 2018) or significant group differences have not been found in volubility (Chapman et al, 2001; Scherer et al, 2008). Likewise, conversational turn count from the LENA automated analysis showed a significant interaction effect between groups and age, where infants with CP showed higher conversational turn counts at 4 to 6 months than infants without CP, but not at later ages.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This study showed that infants with CP produced more child vocalization counts from the LENA automated analysis than infants without at 4 to 6 months and 7 to 9 months but not at later ages. This result was unexpected as previous studies have either reported that children with CP produce fewer vocalizations than children without CP (Philips and Kent, 1984; Chapman, 1991; Ha, 2018) or significant group differences have not been found in volubility (Chapman et al, 2001; Scherer et al, 2008). Likewise, conversational turn count from the LENA automated analysis showed a significant interaction effect between groups and age, where infants with CP showed higher conversational turn counts at 4 to 6 months than infants without CP, but not at later ages.…”
Section: Discussionmentioning
confidence: 56%
“…Perhaps as should be expected given these deficits of speech and hearing mechanisms, the literature has consistently reported that infants with CP show late onset of canonical babbling and fewer consonant types in their inventories of prespeech vocalizations than typically developing infants (Chapman, 1991; Willadsen and Enemark, 2000; Chapman et al, 2001; Ha, 2018; Zajac et al, 2021). For example, Chapman et al (2001) reported that only 57% of infants with CP reached the canonical babbling stage by 9 months compared to 93% of their age-matched peers without CP.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations